Preparation and Characterization of A Nanoliposomal Vaccine of pcLACK Candidate Against Cutaneous Leishmaniasis - Hezarjaribi, Hajar Z.; Soosaraei, Masoud; Fakhar, Mahdi; Akhtari, Javad; Rafiei, Alireza; Jorjani, Oghol Niaz (Infectious Disorders - Drug Targets, 2021)
Background: Leishmaniasis is a public health problem and endemic in countries of the tropics and subtropics. An ongoing project with naked LACK (Leishmania homolog of receptors for activated C-kinase) demonstrated that this case of the gene is entirely susceptible to immune response and it does enter the cells effectively. This study aimed at developing a procedure to prepare a type of lipid nanoparticles overloaded with plasmid LACK (pcLACK) for usage as Leishmania major (L. major) nanoliposomal vaccine. Materials and Methods: The single-gene expression plasmid of pcLACK was encoded in the LACK antigen. Nanoparticles were set up by thin film procedure using cationic lipids 1, 2-Dioleoyl- 3-Trimethylammonium propane (DOTAP), 1, 2-Dioleoyl-snGlycero-3-Phosphoethanolamine (DOPE), and cholesterol in a molar proportion of 2:1:1 molar ratio. Using dynamic light scattering, the particle diameters of empty and loaded lipoplexes were measured in triplicate. The zeta-potential (ζ) was measured with the same instrument using the zeta potential mode as the average of 20 measurements by diluting the particles into a low salt buffer. Results: The results of the sustainability studies of Liposome-pcLACK formulation showed that there were no significant physical changes up to the 30th day of stability study at the storage condition of 4°C. However, there were significant changes in the formulation content during storage at 25°C for 30 days (204.2±0.90 at Day 30 compared with 207.2±0.26 nm at Day 0). It was observed that the prepared nanoliposomal formulation had more stability under refrigeration. Conclusion: Immunostimulatory cationic lipids bearing a pcLACK encapsulation could serve as an effective delivery system.
Keywords: encapsulation